Komitmen Bersama Para Aktor dalam Proses Kolaborasi Pelaksanaan Kebijakan Pungutan Wisatawan Asing sebagai Bentuk Bersama Membangun Bali - Ni Putu Yosinta Dewi; Ni Putu Anik Prabawati (Socio-political Communication and Policy Review, 2025)
This study aims to explain the shared commitment of actors in the collaborative governance process in implementing the policy of foreign tourist levy apllied in Bali Province based on the theory of Ansell & Gash. The research method adopted is a literature study using various reference sources to obtain information about the involvement of government, private, non-government, and the community in the implementation of the policy. The results show that the shared commitment among actors is still not optimal because the amount of levy revenue is very different from the number of foreign tourist arrivals. These are caused by challenges faced by the actors, such as incomplete inspection implementation, less strategic locations of payment counter, uneven dissemination of socialization results, limited availability of international payment systems, cyber threat, and concerns about the end point. Through this commitment, intermediate outcomes has been obtained in the form of levy revenue exceeding 318 billion rupiahs, which has been utilized and planned for custmary villages, subak management, temple management, and art activist performing at the 47th Bali Arts Festival (PKB) as a form of cultural and enviromental protection in Bali Province. For better results, each actors needs to improve in fulfilling their commitments.